Analisis Faktor Multivariat Untuk Mengidentifikasi Penyebab Stress Pada Tenaga Kesehatan - Rifqo, Fannisha Aura; Zakiah, Dalfa; Sholihat, Dhea Amila; Tarman, T (STIKOM Tunas Bangsa Pematangsiantar, 2026)
This study aims to identify and analyze multivariate factors contributing to psychological stress and burnout among healthcare workers using a quantitative approach. Structural Equation Modeling (SEM) was employed to examine the relationships between job-related factors and psychological outcomes, where workload, social support, and work environment conditions were treated as independent variables, while psychological stress and burnout served as dependent variables. Data were collected from 40 healthcare workers using a structured questionnaire with a five-point Likert scale and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that workload has a positive and significant effect on psychological stress, suggesting that increasing job demands elevate stress levels among healthcare workers. Psychological stress was also found to significantly affect burnout, confirming its role as a key mediator between job demands and emotional exhaustion. In addition, work environment conditions demonstrate a significant direct effect on burnout, indicating that unfavorable physical and organizational environments contribute to chronic fatigue and disengagement. Conversely, social support does not show a significant effect on either psychological stress or burnout, which may be influenced by contextual factors or limitations in sample size. Overall, the findings indicate that job demands and work environment conditions are key factors contributing to psychological stress and burnout among healthcare workers, highlighting the need for organizational interventions focused on workload management and improvement of work environment quality.